Methodological problems of FDI statistics in accession countries - Christine Borrmann (Hamburg Institute of International Economics (HWWA), 2003)
Foreign direct investment (FDI) is a crucial indicator for a country's integration into the global division of labour and its general level of development. Empirical analyses of integration processes however require an extensively harmonized procedure to compile and disseminate FDI data. This paper focuses on the question whether and to what extent a comparability of FDI data can be taken for granted. In the recent past, comparability of FDI data has improved a lot: According to IMF surveys in 2001 and 1997, the Applicant Countries (ACs) in particular were rather successful in complying with the international standards. However, a lot of problems remain, especially concerning the inclusion of indirectly owned direct investment enterprises, the comprehensive coverage of FDI components, the reporting of reverse investment and the measurement of stock data. For certain established EU countries the problem of international holding companies causes further complications. Moreover, harmonization in recent years does not necessarily mean respective ex post adjustments. So international comparisons should focus on the very recent years of more successful harmonization and always keep in mind, that deviations might, to a high extent, be due to statistical and methodological reasons.
Keywords: 330